2013
DOI: 10.1039/c3em00208j
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between radioactivity levels and heavy metal content in the soils of the North Kosovska Mitrovica environment

Abstract: This paper reports the results of radioactivity concentrations and heavy metal content in soil samples collected from non-agricultural areas in the municipality and vicinity of North Kosovska Mitrovica, formerly the most important mining area in Europe. The estimated average activity concentrations of (226)Ra, (232)Th, (40)K and (137)Cs are 40.6 ± 19, 48 ± 25.4, 743.2 ± 200.5 and 81 ± 119 Bq kg(-1), respectively. The estimated average absorbed dose rate in the air and the annual effective dose are 78.7 nGy h(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…This study was conducted based on previous research in this mining/industrial area, which is suspected in elevated soil radioactivity, enhanced indoor radon levels and diverse geological characteristics [36,37]. The primary goals of the present paper were to analyze monthly and seasonal indoor radon variations in a typical ground-floor residential house, to assess the possible impact of geology (radioactivity from soil and stone used for construction) and relationships between indoor radon concentrations and main meteorological parameters, such as pressure, temperature, relative humidity and dew point.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted based on previous research in this mining/industrial area, which is suspected in elevated soil radioactivity, enhanced indoor radon levels and diverse geological characteristics [36,37]. The primary goals of the present paper were to analyze monthly and seasonal indoor radon variations in a typical ground-floor residential house, to assess the possible impact of geology (radioactivity from soil and stone used for construction) and relationships between indoor radon concentrations and main meteorological parameters, such as pressure, temperature, relative humidity and dew point.…”
Section: Introductionmentioning
confidence: 99%
“…The ranges of spe cific ac tiv i ties for nat u ral radionuclides de ter mined in this pa per have been found to lie nearly within the oth ers, and their av er age spe cific ac tiv i ties did not dif fer to a great ex tent. The mean of 226 Ra spe cific ac tiv i ties were higher than in most other stud ies ex cept for soil in North Kosovska Mitrovica [12]. Sim i lar 40 K con tent was mea sured in sur face soil in West ern Ser bia [11] and Priština [13].…”
Section: Ta Ble 4 De Scrip Tive Sta Tis Tics Of Spe Cific Ac Tiv I Ties (A S ) Of An a Lyzed Radionuclides In All Soil Sam Plesmentioning
confidence: 58%
“…Much con cern has been ad dressed over the prob lem of soil con tam i na tion with heavy met als and or ganic pol lut ants due to rapid in dus tri aliza tion and ur ban iza tion [3,[7][8][9][10]. At the same time, var i ous radioecological stud ies per formed in Ser bia have been aimed mainly to a de ter mi na tion of the content of radionuclides in ur ban soil of dif fer ent land uses, not ex clu sively pub lic green ar eas, es ti mat ing only risks and health haz ards from the ex ter nal ra di ation ex po sure of the pop u la tion with out tak ing into ac -count spe cific ex po sure sce nar ios [2,4,[11][12][13][14][15][16][17][18]. The lit er a ture re view has shown that there are no data on the ap pli ca tion of US EPA health risk as sess ment meth od ol ogy due to ra di a tion ex po sure of hu mans in Ser bia.…”
Section: Introductionmentioning
confidence: 99%
“…Rani et al (2015) have reported the range of 238 U, 232 Th, and 40 K from 13 to 36 Bq kg −1 , 40 to 71 Bq kg −1 , and 294 to 781 Bq kg −1 in the soil samples of Rajasthan, India. Gulan et al (2013) have reported the range of 238 U, 232 Th, and 40 K from 21.2 to 91.1 Bq kg −1 , 20.3 to 103.8 Bq kg −1 , and 365.1 to 1148.7 Bq kg −1 in North Kosovska, Europe. Asaduzzaman et al (2015) have reported the range of 238 U, 232 Th, and 40 K from 49.4 to 60.5 Bq kg −1 , 64.7 to 82 Bq kg −1 , and 927.2 to 1080.3 Bq kg −1 in Bangladesh.…”
Section: Resultsmentioning
confidence: 99%